Total knee arthroplasty: the future. - Pandit, H; Aslam, N; Pirpiris, M; Jinnah, R (2006)
Few areas in orthopaedics have evolved so dramatically over the past few decades as our knowledge of knee physiology, knee kinematics, and knee replacement surgery. This article addresses major breakthroughs in knee replacement surgery, the thought process behind these concepts, and their impact on clinical practice. It focuses on compartmental arthroplasty, use of minimally invasive surgery, advances in biomaterials, and biological solutions for treating arthritis. Compartmental knee replacements are gaining popularity, especially for medial compartment arthritis. Minimally invasive surgery (i.e., quadriceps sparing arthroplasty) has become very popular in the last few years and is being used routinely for unicompartmental knee replacement and increasingly used for total knee replacement. Computer-assisted surgery has the ability to help the surgeon place the components in the desired position, thereby avoiding component malpositioning, which can cause pain, instability, limited range of movement, excessive polyethylene wear, and subsequent implant loosening. Recent advances in the metallurgy have led to the introduction of tantalum trabecular metal which offers several advantages over other current conventional materials used for implants. Expanding knowledge regarding cartilage biochemistry and the pathogenesis of osteoarthritis has focused the research on slowing the progression of osteoarthritis and promoting cartilage matrix synthesis. Perichondrial transplantation as well as periosteal transplantation have been tried by a few investigators but they have limited and temporary success. Autologous chondrocyte implantation is another technique that is gaining popularity. The chondrocytes harvested from the patient are cultured and reimplanted after 3-4 weeks of culturing. In the future, we are likely to see advances in diagnosis as well as management of osteoarthritis. The treatment modalities will probably evolve at the cellular level and it will not be long before a patient-specific medication can be given to a asymptomatic patient in order to prevent development of osteoarthritis. Patients with end-stage osteoarthritis will be offered a combination of treatments (e.g., partial replacement of one compartment or localized cartilage repair if there is localized cartilage defect in the other compartment).